Tephroseris integrifolia subsp. integrifolia ... - Jarvis, Charlie (Zenodo, 2007)
Othonna integrifolia Linnaeus, Species Plantarum 2: 925. 1753. "Habitat in Alpibus Pyrenaicis, Helveticis, Austriacis, Sibiricis." RCN: 6366. Basionym of: Cineraria alpina (L.) L. var. integrifolia (L.) L. (1763). Type not designated. Original material: Herb. Burser VI: 122 (UPS); [icon] in Gmelin, Fl. Sibirica 2: 154, t. 71. 1752; [icon] in Morison, Pl. Hist. Univ. 3: 111, s. 7, t. 12, f. 28. 1699; [icon] in Clusius, Rar. Pl. Hist. 2: 22. 1601. Current name: Tephroseris integrifolia (L.) Holub subsp. integrifolia (Asteraceae). ... : Published as part of Jarvis, Charlie, 2007, Chapter 7: Linnaean Plant Names and their Types (part O), pp. 696-717 in Order out of Chaos. Linnaean Plant Types and their Types, London :Linnaean Society of London in association with the Natural History Museum on page 715, DOI: 10.5281/zenodo.291971 ...